2020
DOI: 10.3390/ma13235434
|View full text |Cite
|
Sign up to set email alerts
|

Nanoarchitectonics of Lotus Seed Derived Nanoporous Carbon Materials for Supercapacitor Applications

Abstract: Of the available environmentally friendly energy storage devices, supercapacitors are the most promising because of their high energy density, ultra-fast charging-discharging rate, outstanding cycle life, cost-effectiveness, and safety. In this work, nanoporous carbon materials were prepared by applying zinc chloride activation of lotus seed powder from 600 °C to 1000 °C and the electrochemical energy storage (supercapacitance) of the resulting materials in aqueous electrolyte (1M H2SO4) are reported. Lotus se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…In addition, this capacitance value is still higher than other reported results of porous carbon derived from natural resources of jackfruit seed and sorghum biomass-derived porous carbons, which achieved 292.2 F g −1 and 240 F g −1 , respectively, at 5 mV s −1 [ 79 , 80 ]. Activation of Lapsi seed yielded porous carbon with high surface area of 1316.7 m 2 g −1 with a capacitance of 317.5 F g −1 at 5 mV s −1 [ 81 ]. It is interesting to compare the effect of different Lewis acids e.g., FeCl 3 in graphite intercalated compounds when reacted with dodcecyl amine and heated at higher temperatures of 900 °C and 2000 °C without activation to accomplish a surface area of 17 and 53 m 2 g −1 and a capacitance of 42 and 90 F g −1 , respectively [ 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this capacitance value is still higher than other reported results of porous carbon derived from natural resources of jackfruit seed and sorghum biomass-derived porous carbons, which achieved 292.2 F g −1 and 240 F g −1 , respectively, at 5 mV s −1 [ 79 , 80 ]. Activation of Lapsi seed yielded porous carbon with high surface area of 1316.7 m 2 g −1 with a capacitance of 317.5 F g −1 at 5 mV s −1 [ 81 ]. It is interesting to compare the effect of different Lewis acids e.g., FeCl 3 in graphite intercalated compounds when reacted with dodcecyl amine and heated at higher temperatures of 900 °C and 2000 °C without activation to accomplish a surface area of 17 and 53 m 2 g −1 and a capacitance of 42 and 90 F g −1 , respectively [ 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the surface textural-properties, and hence the energy-storage capacity of the biomass carbons, depend on the carbon sources themselves and other carbonization conditions, including the type of activator, carbonization temperature, impregnation ratio of the activator, heating ramp, and hold time [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. For example, our group recently reported the supercapacitance-performance of carbon materials obtained by the ZnCl 2 activation of Nelumbo nucifera (Lotus) seed powder from 600–1000 °C [ 51 ]. The carbon obtained by the carbonization at 800 °C displayed the highest surface area of 1316 m 2 g −1 , and the electrode achieved 272 F g −1 specific capacitance at 1 A g −1 with the superior cycle-life of 99% after 10,000 charging/discharging cycles.…”
Section: Introductionmentioning
confidence: 99%
“…12 Especially, there is a great enhancement in the capacitance value for carbon-based supercapacitor devices. 13,14 Albeit, along with these advantages, cycling stability has been a potential challenge faced by many redox-additive electrolytes. This limits their commercial aspect since stability plays a crucial role in the SC device.…”
Section: Introductionmentioning
confidence: 99%
“…With the presence of redox-additive electrolytes, one can ameliorate the overall cell performance through its pseudocapacitive contribution. During the charge–discharge process, the redox reactions at the electrode material of electrolyte additives act as an active part, conducive to electron transfer across them . Especially, there is a great enhancement in the capacitance value for carbon-based supercapacitor devices. , Albeit, along with these advantages, cycling stability has been a potential challenge faced by many redox-additive electrolytes. This limits their commercial aspect since stability plays a crucial role in the SC device.…”
Section: Introductionmentioning
confidence: 99%